ON A NEW TECHNOLOGY OF PREPARATION OF HOT DRINKING WATER - M. F. Jalilov; M. M. Azimova; A. M. Jalilova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The present article contains information concerning the new Cl-anionization technology in the preparation of hot drinking water. In contrast with water softening, that replaces all the hardness salts by sodium cations in the cation exchanger, this new technology makes it possible to replace incrustating HCO3̄ and SO42--anions in a strong-base anion exchanger by Cl⁻-ions. As a result, the incrustation on the surfaces of heating hot water heaters is prevented. Thus, cations of hardness that are valuable for the human body remain in the water, the quality of the latter conforming to drinking water quality. Considering the important role of calcium and magnesium in the human body, in Germany and Turkey the minimum value of hardness cations in drinking water is limited to 2.85 and 7.50 mg-Eqv/l, respectively. According to the World Health Organization, in the composition of drinking water, the concentration of cations of magnesium and calcium is recommended, respectively, within 10–(20–30), and 20–50 mg/l; the minimum value of total hardness is 2–4 mg-Eqv/l. According to the developed technology drinking water is passed consistently in the downward direction through the mechanical and chlorineanionite exchanger filters. In the latter, the main part of HCO3̄ and SO42--water ions are exchanged for Cl-anions of anionite. Then the water is collected in the tank, from where it is pumped to the hot water heater through the ultraviolet disinfection unit. After the depletion of the anionite by HCO3̄ and SO42--anions, it is regenerated by a solution of 8–12 % NaCl. The results of research by the anion exchangers Purolite A200EMBCl and AB-17-8 are plotted. It is noted that when the specific consumption of salt for regeneration is of about 45–55 kg/m³, working exchange capacity of the A200EMBCl occurs to be in the range 300–370 g-Eqv/m³. For anionization of water, the residual concentration of HCO3̄-ions are changed from 0.5 to 3.2 mg-Eqv/l. The average concentration of these anions occurs to be between 1.8 and 2.2 mg-Eqv/l, when their initial value is 4.4 mg-Eqv/l.